2009
DOI: 10.1007/s11244-008-9176-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Kinetic DFT Characterization of Materials to Rationalize Catalytic Performance

Abstract: This review shortly discusses recent results obtained by the application of density functional theory for the calculations of the adsorption and diffusion properties of small molecules and their reactivity on heterogenous catalytic systems, in the ambit of the Nanocat project. Particular focus has been devoted to palladium catalysts, either in atomic or small cluster form. Some protocols have been tested to obtain efficient ways able to treat the electronic and geometric influence of supports like zeolites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 94 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…Careful consideration was given to the possible occurrence of different spin states by checking the stability of the wave function and accounting for spin contamination (refer to Tables S1 and S2 in the Supporting Information for the expectation value of the total spin, ⟨ S 2 ⟩). The metal-zeolite systems were modeled by the M06-L meta-GGA functional , along with the 6-31g­(d,p) basis for the Al, C, H, and O atoms and the Lanl2DZ basis set and effective core potential for the Ni and Si atoms (for computational efficiency). , Effective core potential offers significant computational savings and has been reported in the literature for understanding chemical reactivity in zeolite-supported metal clusters. , The M06-L functional has been parametrized for transition metal bonding , and employed to model metal clusters in zeolites. , In benchmarking calculations, Truhlar and co-workers have demonstrated that, for binding in zeolite clusters, the M06-L functional gives a mean unsigned error of only 0.87 kcal/mol . Furthermore, the M06-L functional was parametrized to include medium-range dispersion interactions. , All the atoms in the zeolite cluster, including the metal species, were allowed to relax, except for the capping H atoms that were frozen in Cartesian space (see the Supporting Information for details regarding the optimized structures).…”
Section: Methodsmentioning
confidence: 99%
“…Careful consideration was given to the possible occurrence of different spin states by checking the stability of the wave function and accounting for spin contamination (refer to Tables S1 and S2 in the Supporting Information for the expectation value of the total spin, ⟨ S 2 ⟩). The metal-zeolite systems were modeled by the M06-L meta-GGA functional , along with the 6-31g­(d,p) basis for the Al, C, H, and O atoms and the Lanl2DZ basis set and effective core potential for the Ni and Si atoms (for computational efficiency). , Effective core potential offers significant computational savings and has been reported in the literature for understanding chemical reactivity in zeolite-supported metal clusters. , The M06-L functional has been parametrized for transition metal bonding , and employed to model metal clusters in zeolites. , In benchmarking calculations, Truhlar and co-workers have demonstrated that, for binding in zeolite clusters, the M06-L functional gives a mean unsigned error of only 0.87 kcal/mol . Furthermore, the M06-L functional was parametrized to include medium-range dispersion interactions. , All the atoms in the zeolite cluster, including the metal species, were allowed to relax, except for the capping H atoms that were frozen in Cartesian space (see the Supporting Information for details regarding the optimized structures).…”
Section: Methodsmentioning
confidence: 99%
“…The remaining part of the SWCNT was defined as the lower layer and treated by the universal force field (UFF) [27,28]. The position of atoms in this layer was kept frozen, while the Pd 4 clusters were left free to move to the energetically most favored position [29].…”
Section: Models and Computationmentioning
confidence: 99%
“…To our knowledge, the location of the high spin‐low spin intersystem crossing occurring along the reaction coordinate of H 2 dissociation has not been yet reported in the literature. Such study could, in our opinion, shed light on the conditions in which hydrogen species on palladium could explicate their catalytic activity, and it is part of a more extended project devoted to the computational investigation of reduction processes on bare and supported metal catalysts 6–8 (for a review, see 9).…”
Section: Introductionmentioning
confidence: 99%